Thermal performance enhancement of the mixed convection between two parallel plates by using triangular ribs - Jehhef, Kadhum Audaa; Badawy, Faris Ali; Hussein, Alwan Ali (Zielona Góra: Uniwersytet Zielonogórski)
This paper aims to investigate the mixed convection between two parallel plates of a vertical channel, in the presence of a triangular rib. The non-stationary Navier-Stokes equations were solved numerically in a two-dimensional formulation for the low Reynolds number for the laminar air flow regime.
Keywords: numerical study; mixed convection; vertical channel; triangular rib